2017
DOI: 10.1124/dmd.117.076869
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Red Blood Cell–Mediated Rare Xenobiotic Phosphorylation of a Drug Molecule Not Intended to Be a Kinase Substrate

Abstract: Phosphorylation of xenobiotics is rare, probably owing to a strong evolutionary pressure against it. This rarity may have attracted more attention recently as a result of intentionally designed kinase-substrate analogs that depend on kinase-catalyzed activation to form phosphorylated active drugs. We report a rare phosphorylated metabolite observed unexpectedly in mouse plasma samples after an oral dose of a Tankyrase inhibitor that was not intended to be a kinase substrate, i.e., ()-2-(4-(6-(3,4-dimethylpiper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The metabolites falling under this category can thus be easily missed without the relevant experiments, such as the aforementioned siponimod cholesterol ester metabolite M17 (Figure 6B) and a rare erythrocyte-mediated phosphorylation metabolite of AZ2381 not formed in cryopreserved hepatocytes. 121 Sometimes, metabolites from non-host origin, i.e., gut microbiome-derived drug metabolites, can also be efficiently re-absorbed into circulation and appear as a major circulating metabolite, as in the case of the ozanimod oxadiazole ring scission metabolite RP101124 representing 15% of DRM in circulation (Figure 2C). 28 From a human 14 C mass balance study of pimasertib, a novel phosphoethanolamine conjugate metabolite M554 was observed as the major metabolite in circulation (30% of AUC) and in excreta (17% of dose) (Figure 8B).…”
Section: Unexpected Major Metabolites In Circulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The metabolites falling under this category can thus be easily missed without the relevant experiments, such as the aforementioned siponimod cholesterol ester metabolite M17 (Figure 6B) and a rare erythrocyte-mediated phosphorylation metabolite of AZ2381 not formed in cryopreserved hepatocytes. 121 Sometimes, metabolites from non-host origin, i.e., gut microbiome-derived drug metabolites, can also be efficiently re-absorbed into circulation and appear as a major circulating metabolite, as in the case of the ozanimod oxadiazole ring scission metabolite RP101124 representing 15% of DRM in circulation (Figure 2C). 28 From a human 14 C mass balance study of pimasertib, a novel phosphoethanolamine conjugate metabolite M554 was observed as the major metabolite in circulation (30% of AUC) and in excreta (17% of dose) (Figure 8B).…”
Section: Unexpected Major Metabolites In Circulationmentioning
confidence: 99%
“…When the responsible enzymes are unknown or the metabolism is solely from extrahepatic origin, typical in vitro metabolism studies using liver-derived cells and subcellular fractions will not be the appropriate system to capture these metabolites. The metabolites falling under this category can thus be easily missed without the relevant experiments, such as the aforementioned siponimod cholesterol ester metabolite M17 (Figure B) and a rare erythrocyte-mediated phosphorylation metabolite of AZ2381 not formed in cryopreserved hepatocytes . Sometimes, metabolites from non-host origin, i.e., gut microbiome-derived drug metabolites, can also be efficiently re-absorbed into circulation and appear as a major circulating metabolite, as in the case of the ozanimod oxadiazole ring scission metabolite RP101124 representing 15% of DRM in circulation (Figure C) .…”
Section: Unexpected Major Metabolites In Circulationmentioning
confidence: 99%